EFEKTIVITAS SISTEM BIROKRASI PELAYANAN PUBLIK DI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN MINAHASA - LUMANSIK, DENIS PATRICK; LENGKONG, FLORENCE DAICY; PLANGITEN, NOVVA (Sam Ratulangi University, 2019)
Bureaucracy is an important instrument in a society whose presence is inevitable. Bureaucracyis a logical consequence of accepting the hypothesis that the state has a sacred mission that is to prosper itspeople through bureaucratic media, therefore the state must be directly involved in producing public goodsand services needed by its people. The state is actively involved in the social life of its people even if it isnecessary for the state to decide what is best for its people. For this reason, the state builds an administrativesystem that aims to serve the interests of its people, which is called the bureaucracy. Current conditionsobtained in the regions indicate that the implementation of public services is still faced with a governmentsystem that has not been effective and efficient and the quality of human resources of the apparatus isinadequate. This can be seen from the still many complaints on complaints from the public both directly andthrough mass media, such as convoluted procedures, there is no certainty in the period of settlement, costs tobe incurred, less transparent requirements, the attitude of officers who are less responsive and etc. Giving riseto a bad image that is not good for the government image in the eyes of its own people, especially in the eyesof ordinary people who do not know anything about bureaucracy. Basically, effectiveness is a level of successin achieving goals. Stating that effectiveness comes from the word effectives which means the extent to whichor to what extent the group reaches its goal. The system is a set of elements that are interrelated and influenceeach other in carrying out joint activities to achieve a goal, the bureaucracy is a system of government that isrun by government employees because it has held to the hierarchy and levels of office. Service is an action onthe actions of a person or organization to provide satisfaction to customers of a product or a service that theyneed. This research then this research uses descriptive qualitative research methods. The services provided bythe Population and Civil Registry Office cannot be said either because the management of documents has notbeen running optimally, the program system in Capil is still often experiences disruptions as a result of the e-ID card manufacturing process being hampered. the services provided are still not good either because theexisting services are still not quickly captured and consequently the public service process is hampered.Keywords: Evectivity, System Bureaucracy, Public Service.